2020
DOI: 10.17485/ijst/2020/v13i05/145593
|View full text |Cite
|
Sign up to set email alerts
|

Equipment Sizing and Method for the Application of Exhaust Gas Waste Heat to Food Crops Drying Using a Hot Air Tray Dryer

Abstract: Objectives: Equipment sizing and method of utilizing exhaust gas waste heat for food crops drying are presented. Methods/findings: The sizing of the components of the equipment was achieved using known design principles. The system uses an axial flow turbine and a heat exchanger to harness the energy of the exhaust gas of a diesel engine generator. A 250 kVA generator with measured exhaust gas flow rate and temperature of 44.5 m 3 /min and 382.7 °C was selected for this work. The purpose of the recovered energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 5 publications
0
14
0
3
Order By: Relevance
“…As human population and urbanization grow, there is a concomitant increase in energy use that translates into significant increases in fuel costs [1,2]. Diminishing supplies of petroleum and progressive rise in fuel prices are influencing governments and industries to seek for ways of improving the energy efficiency of engines [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As human population and urbanization grow, there is a concomitant increase in energy use that translates into significant increases in fuel costs [1,2]. Diminishing supplies of petroleum and progressive rise in fuel prices are influencing governments and industries to seek for ways of improving the energy efficiency of engines [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…As human population and urbanization grow, there is a concomitant increase in energy use that translates into significant increases in fuel costs [1,2]. Diminishing supplies of petroleum and progressive rise in fuel prices are influencing governments and industries to seek for ways of improving the energy efficiency of engines [2,3]. Woolley et al [4] reported that up to one third of the global energy consumption is attributable to the industrial sector, with about fifty percent mainly wasted as heat.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the high cost of fuels required to generate power to operate production equipment and machines is also driving research on internal combustion (IC) engine efficiency optimization. Improved conversion of energy in engines gives rise to reduced energy costs globally [2,3]. Lee et al, [4] reported that the waste heat recovery has proved viable in improving the efficiency of IC engines.…”
Section: Introductionmentioning
confidence: 99%